2020
DOI: 10.1155/2020/8896812
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Disinfection of a Dental Clinic during the Covid-19 Pandemic: A Narrative Insight

Abstract: Background. The control of biological hazard risk in health care and dental clinic environments represents a critical point in relation to the Covid-19 infection outbreak and international public health emergency. The purpose of the present review was to evaluate the scientific literature on the no-touch disinfection procedures in dental clinics aiming to limit transmission via airborne particles or fomites using no-touch procedures for environmental decontamination of dental clinics. Methods. An electronic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 96 publications
(101 reference statements)
0
40
0
Order By: Relevance
“… 29 It should be noted that mist applications have already been approved for eyelid infection management, 20 skin 23 and cosmetics 30 with repeated daily exposure for a set period of time. Other reviews by Block and Rowan 31 and Scarano et al 32 found that hypochlorous acid had high predictability and low cost to disinfect against COVID-19 in oral-maxillofacial clinics by spraying small aerosol particles. This review calls for more investigations into the effect of HOCl in mist and fog form on the skin, eyes, and respiratory system when exposed in the proposed smart prefabricated sanitising chamber, especially in the presence of organic substances.…”
Section: A Potential Disinfectantmentioning
confidence: 99%
“… 29 It should be noted that mist applications have already been approved for eyelid infection management, 20 skin 23 and cosmetics 30 with repeated daily exposure for a set period of time. Other reviews by Block and Rowan 31 and Scarano et al 32 found that hypochlorous acid had high predictability and low cost to disinfect against COVID-19 in oral-maxillofacial clinics by spraying small aerosol particles. This review calls for more investigations into the effect of HOCl in mist and fog form on the skin, eyes, and respiratory system when exposed in the proposed smart prefabricated sanitising chamber, especially in the presence of organic substances.…”
Section: A Potential Disinfectantmentioning
confidence: 99%
“…In the assessment of the contagion of saliva, it is important to consider the “ time of physical decay ” depending on the droplets size (Flügge’s droplets), the speed of emission (sneeze or cough), the moisture content in the room and the air exchange, and the “ biological decay ”, namely how long the virus keeps infecting in saliva droplets. The biological decay is caused by dehydration, ultraviolet rays, and chemical products [ 39 , 40 , 41 ]. There are some studies performed about the persistency of the 2019-nCoV in aerosol and different surfaces (plastic, steel, copper, carton) [ 24 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biological decay depends on temperature (at 30–40 °C, virus expires), and at a temperature of less than 4 °C, SARS-CoV-2 may remain active for up to 28 days. Using for the disinfection of surfaces: 0.1% sodium hypochlorite or 62–71% ethanol coronavirus notably reduces its infecting action on the surfaces within 1 min of exposure [ 28 , 40 , 43 , 49 , 50 , 51 ]. Shanna Ratnesar-Shumate et al showed some encouraging results about the capacity of the sun light to quickly disactivate the SARS-CoV-2 virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novelty of COVID-19 pandemic -along with its uncertainties -makes it critical for health authorities to develop appropriate medical equipment and environmental disinfection regulations to keep the safety for both patients and clinicians in the countenance of the current COVID-19 pandemic. 26 The oft-cited Healthcare Infection Control Practices Advisory Committee (HICPAC) and Centers for Disease Control and Prevention (CDC) guidelines, advocating for non-critical medical equipment, such as stethoscopes, should be disinfected once daily or weekly. 6 The above standards might not be reflective on the current danger that a contaminated stethoscope may feasibly jeopardize patients' and physicians' safety -given the survival potential of coronavirus to thrive on different surfaces for an extended period of time.…”
Section: Introductionmentioning
confidence: 99%